Transformation of biophysical education at a medical university in the context of digitalisation - Khilmanovich, Valiantsina N. (University Pedagogical Journal, 2025)
The transformation of biophysics education in the context of transition from a classical medical university to a digital one is considered. The emergence and development of two approaches to the interpretation of the concept of biophysics, biophysics as a science and biophysics as an academic discipline of a medical university, are analysed. The stages of development of biophysics as a science are highlighted. The expansion of the concept of the educational discipline «Biophysics» in the conditions of digitalisation is shown. The connection of biophysical education and its content with the formation of new professional competences of a future doctor is determined. The extended definition of the concept of «biophysical education at a medical university» is proposed, the tasks to be solved for its further application in pedagogical practice are defined.